Analisis Efisiensi Dan Efektivitas E-Government Dalam Administrasi Publik - Deby Novalia Gultom; Etika Khairina; Lubna Salsabila (UIR Press, 2024)
E-Government has become central to the transformation of public administration, offering various possibilities to improve the efficiency and effectiveness of government services. This analysis investigates how the implementation of e-government affects public administration from the perspective of operational efficiency and achievement of public service objectives. In addition, E-government is the vanguard of efforts to provide information and services to citizens, businesses, employees and government units, and other organizational sectors. This study adopts a qualitative approach where the sources collected come from journals, books. The results show that the efficiency and effectiveness of e-Government in public administration related to the application of information technology has a significant positive impact. E-Government is also able to increase efficiency in the delivery of public services by cutting bureaucracy and speeding up administrative processes. Simultaneously, the effectiveness of e-Government is reflected in faster responses to citizen needs, enhanced transparency, and increased citizen participation in public decision-making.